ANALISIS KETERLAMBATAN PENYAMPAIAN LAPORAN KEUANGAN DAN KINERJA KEUANGAN STUDI PADA PERUSAHAAN PUBLIK 1999-2005 - TRI GUNARSIH (Universitas Islam Nahdlatul Ulama Jepara, 2010)
ABSTRACT The main objective of this study is to analyze timelines of financial statement reporting and financial performance in Indonesian Stock Exchange (IDX). Samples In this study are IDX public companies listed In 1999-2005, The research questions are tested by running ANOVA to analyze whether any differences in timelines of financial statement reporting and finanda/performance between years and between size and also Independent i test to analyze whether any differences in timelines of financial statement and financial penvnffance between industry. Timelines (KW) proxied by dummy variable, If companies published financial reporting before 120 days after December 31 and 0 otherwise. finandaf performance proxied by Sales, Asset Earning After Tax(EAT)f Return on Investment (ROI), Return on Equity (ROE), and Sales Growth. The results of between year comparisons show that there are differences (increasing) between years for EAT, ROI and KW. These suggest that firm performance and timelines of finandaf statement reporting are increasing over time. The results of between size comparisons show that there are differences between size for EAT, Sales and KW. The bigger the size, the higher the financial performance and the timelines. The results of between industry comparisons show that there are differences for Asset and EAT. Base on these variables, financialperformance in service industry higher than manufacture industry.